Therapeutic principles and unmet needs in the treatment of cough in pediatric patients: review and expert survey - Christian Vogelberg; Francisco Cuevas Schacht; Christopher P. Watling; Laura Upstone; Georg Seifert (BMC, 2023)
Abstract Background There are evidence gaps in the management of pediatric cough, particularly for acute pediatric cough. This study had two aims: to identify therapeutic principles and unmet needs in the treatment of cough in pediatric patients (internationally), and to consider the evidence required to address these unmet needs. Methods A MEDLINE/PubMed database search was performed to identify articles describing therapeutic principles in the treatment of pediatric cough. An online survey of international pediatric cough experts was conducted, with questions on the definitions, diagnosis, treatment, and unmet needs in pediatric cough management. Results Cough guidelines have differing definitions of pediatric patients (≤12-18 years), acute pediatric cough (< 2-3 weeks), and chronic pediatric cough (> 4-8 weeks). Similarly, among 18 experts surveyed, definitions varied for pediatric patients (≤10-21 years), acute pediatric cough (< 3-5 days to < 6 weeks), and chronic pediatric cough (> 2-8 weeks). Guidelines generally do not recommend over-the-counter or prescription cough medicines in acute pediatric cough, due to lack of evidence. In the expert survey, participants had differing opinions on which medicines were most suitable for treating acute pediatric cough, and noted that effective treatments are lacking for cough-related pain and sleep disruption. Overall, guidelines and experts agreed that chronic pediatric cough requires diagnostic investigations to identify the underlying cough-causing disease and thereby to guide treatment. There are unmet needs for new effective and safe treatments for acute pediatric cough, and for randomized controlled trials of existing treatments. Safety is a particular concern in this vulnerable patient population. There is also a need for better understanding of the causes, phenotypes, and prevalence of pediatric cough, and how this relates to its diagnosis and treatment. Conclusions Whereas pediatric cough guidelines largely align with regard to the diagnosis and treatment of chronic cough, there is limited evidence-based guidance for the management of acute cough. There is a need for harmonization of pediatric cough management, and the development of standard guidelines suitable for all regions and patient circumstances.